La venta de tierras baldías : el comunitarismo agrario y la corona de Castilla durante el siglo XVI / David E. Vassberg ; [versión Española, David Pradales Ciprés...et al.] - Pradales Cipres, David; Vassberg, David E. (Estudios)
Bibliografía. Índices